The Oxford handbook on the World Trade Organizatio - Narlikar, Amrita (Oxford, 2012)
The Oxford Handbook on the World Trade Organization provides an authoritative and cutting-edge account of the World Trade Organization. Its purpose is to provide a holistic understanding of what the WTO does, how it goes about fulfilling its tasks, its achievements and problems, and how it might contend with some critical challenges. The Handbook benefits from an interdisciplinary approach. The editorial team